Fermentação ruminal e digestibilidade em bovinos recebendo dietas com ou sem adição de extrato tanífero de Acacia mearnsii - Ávila, Suélen Capa de (2013)
This study was conducted to evaluate the addition of 1.5% Acacia mearnsii tannin extract in the total diet of cattle on ruminal fermentation, digestion and retention of N. The experiment was conducted in a 4 x 4 Latin Square design with four steers (263 ± 57 kg of body weight (BW)) housed in metabolism cages. Steers were adapted to diets for 10 d followed by a 5-d collection period. The diet consisted of 70% corn silage and 30% concentrate (dry matter basis (DM)), which included protein source such as soybean meal (SBM) or canola meal (FC) with or without addition of Acacia mearnsii tannin extract. Corn silage and concentrate were mixed offered twice daily (8:00 and 17:00). Feed was offered in an amount restricted to 2,5% of BW. The inclusion of tannin extract had no effect on ruminal concentrations of ammonia N, N α-amino, sugars and ruminal pH. The true and apparent total tract digestibility of OM in the diet were negatively affected by treatments. N retention and urinary excretion was similar between treatments (P <0.05). The rumen digestibility of organic matter decreased with the addition of tannin extract (P <0.05). The synthesis and efficiency of microbial protein were not affected by the inclusion (P <0.05). More studies are conducted in order to determine an appropriate level of Acacia mearnsii tannin extract of in order to increase the supply of metabolizable protein without reducing the digestibility of the diet.